Marker assisted selection (MAS) for downy mildew resistance in grapevines using Rpv3.1 associated markers - AKKURT, Murat; ŞENSES, Irem; AKTÜRK, Burak; TOZLU, Ilhami; ÖZER, Nuray; UZUN, Halil Ibrahim (Notulae botanicae Horti agrobotanici Cluj-Napoca, 2022)
Powdery mildew and downy mildew are primary fungal diseases that cause significant damage in viticulture. Therefore, breeding powdery and/or downy mildew resistance is one of the priority subjects in grapevine breeding programs. This study aims to conduct early-selection by marker assisted selection (MAS) method among 869 genotypes obtained through crossbreeding ‘Alphonse Lavallee’ × ‘Regent’ cultivars using the markers (GF18-06 and GF18-08) associated with downy mildew resistance gene region Rpv3.1 to develop new grapevine cultivars resistant to downy mildew caused by Plasmopara viticola.  A total of 869 hybrid plants which were obtained after crossing ‘Alphonse Lavallee’ × ‘Regent’ in a 3-year breeding program were used in the study. The hybrid plants were scored for the resistance level based on their sporulation intensity after artificial inoculation of P. viticola. DNA samples of the hybrid plants were amplified with GF18-06 and GF18-08 markers in Polymerase Chain Reaction (PCR) for MAS. The alleles which were associated to Rpv3.1 resistance locus and the results of resistance scoring were compared, and the applicability of the markers in MAS was verified. It was determined that the GF18-08/410 bp marker can be used successfully for MAS. Gf 18-06 marker 385 bp, 390 bp and 407 bp gave false positive results in our population, respectively 8.86%, 9.02% and 37.94%. Therefore, this may limit its use for MAS.